2021
DOI: 10.1002/esp.5213
|View full text |Cite
|
Sign up to set email alerts
|

Modelling sediment (dis)connectivity across a river network to understand locational‐transmission‐filter sensitivity for identifying hotspots of potential geomorphic adjustment

Abstract: Rivers act as ‘jerky conveyor belts’ that transmit fluxes of flow and sediment downstream. This transmission of fluxes can be highly variable within a drainage basin resulting in either abrupt or gradational sediment (dis)connectivity patterns and processes. This study assesses sediment (dis)connectivity across a basin as a means to understand the locational, transmission and filter sensitivity properties of a fluvial system. Drawing upon the case study of Richmond River Catchment, New South Wales, Australia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Poeppl et al, In press). In this SI, five contributions have dealt with connectivity in mountain environments, with a specific focus on fluvial processes by Hinshaw et al (2022; South Fork McKenzie River basin, Cascade Mountains, Oregon, USA), Kemper et al (2022; Yampa River basin, Rocky Mountains, Colorado, USA), and Khan et al (2021; Richmond River catchment, Great Dividing Range, Australia), on hillslope processes by Martini et al (2022; Rio Cordon catchment, Italian Alps), or on both environments as shown by Turley et al (2021; Tahoma Creek catchment, Cascade Mountains, Washington, USA). Two papers investigated connectivity relationships in river and catchment systems (Bizzi et al, 2021: Vjosa River, Albania; González‐Romero et al, 2021: Segura River catchment, Spain), while two contributions had a specific focus on delta, estuary and wetland environments (Hiatt et al, 2022; Singh et al, 2022; Sonke et al, 2022).…”
Section: Environments and Geomorphic Process Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poeppl et al, In press). In this SI, five contributions have dealt with connectivity in mountain environments, with a specific focus on fluvial processes by Hinshaw et al (2022; South Fork McKenzie River basin, Cascade Mountains, Oregon, USA), Kemper et al (2022; Yampa River basin, Rocky Mountains, Colorado, USA), and Khan et al (2021; Richmond River catchment, Great Dividing Range, Australia), on hillslope processes by Martini et al (2022; Rio Cordon catchment, Italian Alps), or on both environments as shown by Turley et al (2021; Tahoma Creek catchment, Cascade Mountains, Washington, USA). Two papers investigated connectivity relationships in river and catchment systems (Bizzi et al, 2021: Vjosa River, Albania; González‐Romero et al, 2021: Segura River catchment, Spain), while two contributions had a specific focus on delta, estuary and wetland environments (Hiatt et al, 2022; Singh et al, 2022; Sonke et al, 2022).…”
Section: Environments and Geomorphic Process Domainsmentioning
confidence: 99%
“…The spatial dimensions of (dis)connectivity focused on in this SI are likely representative of the distribution of studies in general, where most focus is on the role of longitudinal connectivity of water, sediment and plant propagules. There is a clear focus on longitudinal connectivity of sediment (Bizzi et al, 2021; Kemper et al, 2022; Khan et al, 2021; Turley et al, 2021), followed by that of water fluxes in estuarine channels and wetlands (Hiatt et al, 2022; Sinha et al, 2022). Three studies combined aspects of longitudinal and lateral connectivity, either in the channel‐floodplain (Hinshaw et al, 2022) or the catchment perspective (González‐Romero et al, 2021; Turley et al, 2021).…”
Section: Spatial Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…lakes and ponds) to compute budget components and reveal human impacts (Foster et al, 2021). Laboratory analyses of sediment samples have provided an indirect means of estimating proportional source contributions by 'fingerprinting' sediment characteristics (Pulley et al, 2017;Walling et al, 1998Walling et al, , 2006, with further advances extending the spatial and temporal scales of quantification using information from aerial and satellite imagery, lidar data and modelling (Bizzi et al, 2021;Khan et al, 2021;Piégay et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rivers act as a network of channels that carry water, sediment, and energy downstream (1). On the heterogeneous area of the watershed, some areas might be responsive to disturbance events (e.g., wildfires and droughts), while others may be resistant to the change (Khan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%